I dati Invalsi uno strumento per la ricerca - Falzetti, Patrizia (FrancoAngeli, 2018)
The volume contains a collection of contributions presented at the conference "INVALSI data: a tool for research", held in Rome the 20th September 2016. On this occasion, scholars from different professional contexts (school, university, research) and selected through a call for papers presented their scientific works, using INVALSI data. The book is divided into two parts: the first part devoted to the use of INVALSI data in didactic research, the second focused on INVALSI data as a tool for supporting policy and decision makers. The eighteen chapters cover in-depth analyses that, starting from different angles and using several methodologies, offer the reader a rich and structured view of the different possible uses of the data that INVALSI gather each year.